Deep brain stimulation electrode position impact on parkinsonian non-motor symptoms - Bardon, Jan; Kurcova, Sandra; Chudackova, Monika; Otruba, Pavel; Krahulik, David; Nevrly, Martin; Kanovsky, Petr; Zapletalova, Jana; Valosek, Jan; Hlustik, Petr; Vastik, Miroslav; Vecerkova, Marketa; et al. (Biomedical papers, 2022)
Background. In this study we evaluated the impact of location of deep brain stimulation electrode active contact in different parts of the subthalamic nucleus on improvement of non-motor symptoms in patients with Parkinson's disease. Methods. The subthalamic nucleus was divided into two (dorsolateral/ventromedial) and three (dorsolateral, medial, ventromedial) parts. 37 deep brain stimulation electrodes were divided according to their active contact location. Correlation between change in non-motor symptoms before and one and four months after deep brain stimulation electrode implantation and the location of active contact was made. Results. In dividing the subthalamic nucleus into three parts, no electrode active contact was placed ventromedially, 28 active contacts were located in the medial part and 9 contacts were placed dorsolaterally. After one and four months, no significant difference was found between medial and dorsolateral positions. In the division of the subthalamic nucleus into two parts, 13 contacts were located in the ventromedial part and 24 contacts were placed in the dorsolateral part. After one month, significantly greater improvement in the Non-motor Symptoms Scale for Parkinson's disease (P=0.045) was found on dorsolateral left-sided stimulation, but no significant differences between the ventromedial and dorsolateral positions were found on the right side. Conclusion. This study demonstrated the relationship between improvement of non-motor symptoms and the side (hemisphere, left/right) of the deep brain stimulation electrode active contact, rather than its precise location within specific parts of the subthalamic nucleus in patients treated for advanced Parkinson's disease.
Keywords: non-motor symptoms; Parkinson's disease; deep brain stimulation